Unmapping green space: Discursive dispossession of the right to green space by a compact city planning epistemology. Issue 1 (2nd January 2022) - Zalar, Alva; Pries, Johan
Abstract : In this article, we study the ongoing redevelopment of post-war, modernist residential area Rosengård, located in Sweden's third biggest city Malmö. We show how a planning and design strategy for this area has come to focus on a 'compact city' typology in line with Malmö's strategy for creating a 'near, dense, green and mixed city'. Such compact city typology emphasizes high density, urbanity, proximity and mixed-use as key values for renewal, but also threatens the green spaces in areas designated for densification. This article illustrates how renewal plans for modernist residential areas with generous green space provision also ensure dispossession of residents' rights to green space. Our analysis highlights how this planned dispossession is preceded by a discursive dispossession carried out by the way urban planning represents these spaces. The Rosengård case illustrates how a compact city vision imposed on marginalized modernist areas co-emerges with new forms of expert knowledge which both 'unmaps' existing green spaces and defines them as problematic and requiring interventions. The article highlights the important, but not yet sufficiently explored, dispossession of the right to public green space in racialized poor peripheries of Northern cities already facing intense displacement pressure. We argue that this type of renewal of modernist areas not only tends to neglect mapping important public spaces and uses of space, but actively produces blind spots by deploying a compact city planning epistemology which necessarily undermines rights to green space in the city and should put into question the compact city as the default sustainability fix.